Up-regulated desaturase and elongase gene expression promoted accumulation of polyunsaturated fatty acid (PUFA) but not long-chain PUFA in lates calcarifer, a tropical euryhaline fish, fed a stearidonic acid- and ?-linoleic acid-enriched diet - Alhazzaa, Ramez; Bridle, A.; Nichols, P.; Carter, C. (2011)
The limited activity of 6 fatty acid desaturase (FAD6) on a-linolenic (ALA, 18:3n-3) and linoleic (LA, 18:2n-6) acids in marine fish alters the long-chain (ge;C 20) polyunsaturated fatty acid (LC-PUFA) concentration in fish muscle and liver when vegetable oils replace fish oil (FO) in aquafeeds. Echium oil (EO), rich in stearidonic acid (SDA, 18:4n-3) and ?-linoleic acid (GLA, 18:3n-6), may enhance the biosynthesis of n-3 and n-6 LC-PUFA by bypassing the rate-limiting FAD6 step. Nutritional and environmental modulation of the mechanisms in LC-PUFA biosynthesis was examined in barramundi, Lates calcarifer, a tropical euryhaline fish. Juveniles were maintained in either freshwater or seawater and fed different dietary LC-PUFA precursors present in EO or rapeseed oil (RO) and compared with FO. After 8 weeks, growth of fish fed EO was slower compared to the FO and RO treatments. Irrespective of salinity, expression of the FAD6 and elongase was up-regulated in fish fed EO and RO diets, but did not lead to significant accumulation of LC-PUFA in the neutral lipid of fish tissues as occurred in the FO treatment. However, significant concentrations of eicosapentaenoic acid (EPA, 20:5n-3) and arachidonic acid (ARA, 20:4n-6), but not docosahexaenoic acid (DHA, 22:6n-3), appeared in liver and, to a lesser extent, in muscle of fish fed EO with marked increases in the phospholipid fraction. Fish in the EO treatment had higher EPA and ARA in their liver phospholipids than fish fed FO. Endogenous conversion of dietary precursors into neutral lipid LC-PUFA appears to be limited by factors other than the initial rate-limiting step. In contrast, phospholipid LC-PUFA had higher biosynthesis, or selective retention, in barramundi fed EO rather than RO. © 2011 American Chemical Society.